2011
DOI: 10.1128/mcb.05541-11
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Control of p53 Translation by REDD1 and mTORC1 Limits the p53-Dependent DNA Damage Response

Abstract: Exquisite control of the level and activity of p53 are required in order to preserve cellular homeostasis following DNA damage. How this regulation is integrated with other key metabolic pathways in vivo is poorly understood. Here, we describe an endogenous feedback circuit for regulation of p53 through its transcriptional target gene, Redd1, a stress-induced inhibitor of TOR complex 1 (TORC1) activity. Cells and tissues of Redd1 ؊/؊ mice exhibit enhanced sensitivity to ionizing radiation and chemotherapy trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 38 publications
1
41
1
1
Order By: Relevance
“…mTORC1 can be activated downstream of AKT, and previous studies have suggested mTORC1 can promote p53 protein synthesis. 23,25 However, in our studies the mTORC1 inhibitor rapamycin did not reduce p53 accumulation in Nutlin treated cells (Fig. 3).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…mTORC1 can be activated downstream of AKT, and previous studies have suggested mTORC1 can promote p53 protein synthesis. 23,25 However, in our studies the mTORC1 inhibitor rapamycin did not reduce p53 accumulation in Nutlin treated cells (Fig. 3).…”
Section: Discussioncontrasting
confidence: 52%
“…In contrast, we and others found that the IGF-1R/AKT/mTORC1 signaling promotes p53 protein synthesis and maintains p53 expression levels in stressed cells. [22][23][24][25] These findings raise the possibility that heightened IGF-1R/AKT/mTORC1 activation could potentially increase cancer cell sensitivity to Nutlin by maintaining high p53 protein levels. Finally, we recently found the autophagy inhibitors bafilomycin A1 and chloroquine could increase apoptosis sensitivity in Nutlin treated cells, indicating that autophagy promotes apoptosis resistance.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, it has been reported that DDIT4−/− cells have increased sensitivity to DNA damage in terms of apoptotic response with respect to doxorubicin and radiation, both in vitro and in vivo , in the setting of abnormally increased p53 protein and activity [21]. This could imply that upregulation of DDIT4 would decrease p53 and make cells less sensitive to DNA damage and thus chemotherapy and/or radiation.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is via mechanistic target of rapamycin (mTOR) kinase, which can be activated by growth signals and regulates mRNA translation via assembly of eukaryotic translation initiation factor (eIF) complex (30). For example, inhibition of mTOR decreases p53 translation (31) whereas knockout of protein regulated in development and DNA damage response 1, a stress-induced inhibitor of mTOR1, increases p53 translation (32). The other possibility is that Ninj1-mediated signals may modulate the assembly of translation initiation complex such as eIF4F complex (4E+4G+4A), eIF4B, and poly(A)-binding protein (33).…”
Section: Lack Of Ninj1 Up-regulates P53 Expression Potentially Throughmentioning
confidence: 99%